Risk and meaning adversaries in art, science and philosophy - Bouleau, Nicolas (New York, 2011)
This richly illustrated book is an exploration of how chance and risk, on the one hand, and meaning or significance on the other, compete for the limelight in art, in philosophy, and in science. In modern society, prudence and probability calculation permeate our daily lives. Yet it is clear for all to see that neither cautious bank regulations nor mathematics have prevented economic crises from occurring time and again. Nicolas Bouleau argues that it is the meaning we assign to an event that determines the perceived risk, and that we generally turn a blind eye to this important fact, because the word meaning is itself awkward to explain. He tackles this fundamental question through examples taken from cultural fields ranging from painting, architecture, and music, to poetry, biology, and astronomy. This enables the reader to view overwhelming risks in a different light. Bouleau clarifies that the most important thing in a time of uncertainty is to think of prudence on a higher level, one that truly addresses the various subjective interpretations of the wor
Entrance: Interpretation and Paradigms.- I. Cicero and Divination -- II. Cournot's Philosophic Probabilities -- III. Mathematical Probabilities -- IV. Democracy by Chance -- V. Gestalt, Structure, Pattern -- VI. The Third Dimension of Risk -- VII. Modern Architecture -- VIII. The Ideal City -- IX. Daring the Abstract in Art -- X. Saussure or the Dread of Mathematical Probabilities -- XI. Jacques Monod's Roulette -- XII. From Fortuitism to Animism.- XIII. The Slip as Fortuity and Meaning -- XIV. Guessing Astronomy -- XV. The Legitimacy of Science and Love -- Hints and Ind
Keywords: Risk assessment; Aesthetics; Genetic epistemology; Distribution (Probability theory); Mathematics